Analisis Evaluasi Tata Letak Fasilitas dengan Pendekatan Layout Solution: Studi Kasus Cahaya Grosir Indah Bogor - Nadira Marsandri Ratnakaniya; Azryl Gustian Azhar; Almalia Pramena (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
Cahaya Grosir Indah is a retailer that sells various foodstuffs, clothing, electronics and other general goods. In this research, Cahaya Grosir Indah is the retail store we chose, whether there is an inappropriate layout of the store facilities. This research aims to help optimize the layout design of retail facilities using the Activity Relationship Chart (ARC) method which focuses on analyzing the relationship between activities in retail stores and Total Closeness (TCR) which focuses on the degree of closeness of each room facility in the Cahaya retail business. Indah Wholesale to set top priorities in retail development. Based on the results of the Activity Relationship Chart (ARC) calculation at Cahaya Grosir Indah, the first facility that was prioritized because the results were the highest was the cashier with a TCR (Total Closeness Rating) score of 162, product shelves with a score of 126, warehouse with a score of 34, facility center with a value of 94, and toilets with a value of 18. Therefore, for retail it is important to place other facilities with high value results and are prioritized so that they can be close to each other and facilitate operational processes. The layout has a strategic impact in the longer term. A strategic and comfortable layout provides benefits for retailers to make it easier to organize efficient layout positions and can reduce the density of activity in retail and make it easier for customers to shop.